Gone with the wand : a fairy's tale - Palatini, Margie (Orchard Books, 2009)
When tooth fairy Edith B. Cuspid finds her friend Bernice Sparklestein, a fairy godmother whose work is legendary, having a very bad wand day, she tries to cheer her up by suggesting Bernice try other fairy jobs.